Crypto Embedded System for Electronic Document - Ahmad, Illiasaak; M.Thamrin, Norashikin; Hani, Mohamed Khalil (School of Postgraduate Studies, UTM, 2006)
In this paper, a development of low-cost RSA-based Crypto Embedded System targeted for electronic document security is presented. The RSA algorithm is implemented in a re-configurable hardware, in this case Field Programmable Gate Array (FPGA). The 32-bit soft cores of AlteraÂ’s Nios RISC processor is used as the basic building blocks of the proposed complete embedded solutions. AlteraÂ’s SOPC Builder is used to facilitate the development of crypto embedded system, particularly in hardware/software integration stage. The use of Cryptographic Application Programming Interface (CAPI) to bridge the application and the hardware, and the associated communication layer in the embedded system is also discussed. The result obtained shows that the crypto embedded system provides a suitable compromise between the constraints of speed, space and required security level based on the specific demands of targeted applications.